Levels of Carbon Monoxide Expiratory Air on Shisha Users and the Factors Affecting - Mirsyam Ratri Wiratmoko; Chandrika Karis Adhalia (Jurnal Respirologi Indonesia, 2019)
Background: Shisha is one method of consuming tobacco similar to cigarette but in a different form. Lately it became a trend in Indonesian people, especially teenagers, without knowing any hazards contained in shisha which could cause cancer or even death. Lack of study about shisha in Indonesia was the main reason to do this study so further impact of shisha could be understood. Methodology: This study was analytical observational with cross sectional design. Data of this study was obtained from examination using CO analyzer and from questionnaire filling by respondents from the shisha Bogor community and smokers in Bogor. Results: Among 60 samples we obtained mean expiratory air CO levels of 8,62 ppm for smokers and 20,67 ppm for shisha users. There were also a significant correlation between shisha consumption duration per times and CO expiratory air levels, with P-value of 0,004 and odds ratio 12,52. Conclusion: Expiratory air CO levels in shisha users were higher than smokers, also there were a significant correlation between shisha consumption duration per times and the increasing levels of expiratory air CO. (J Respir Indo 2019; 39(1): 37-43)